The radical transformations and deep continuities of a decade: Turkish educational policy, 1938-1950 - Gunduz, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
Turkey witnessed many educational and cultural policy innovations between 1938 and 1950. Realising strictly secular practices against religion and traditional culture pre-1946, political elites of the time aimed to construct a humanistic culture unique to Turkey. Educational policies were considered the most efficient tools in reaching this ideal. Despite the adverse economic conditions of the time, western cultural institutions were adopted without reservation for modernisation. It was throughout the same time period that a number of other innovative projects such as the village institutes, western translations, new journals, Turkish encyclopaedism, and physical education for the entire public were undertaken. However, as these developments were devoid of a solid historical and sociological foundation, they were forced to change under the new world order post-1945. Despite the changing perspectives on religion, history and cultural life, the policies of the Ismet Inonu era succeeded in carrying the heritage of the Kemalist era to our day. The true dynamics behind this success are the educational practices of the 1940s and their formal and hidden curricula and rituals.
Keywords: democratisation; 1940s; religious education; village institutes; public education; Turkish educational policy; radicalism; Education & Educational Research; Social Sciences - Other Topics